43rd AIAA Aerospace Sciences Meeting and Exhibit 2005
DOI: 10.2514/6.2005-185
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Characterization of Open Lattice Structures Used as Heat Exchanger Surfaces

Abstract: Numerical simulation is performed to evaluate flow field and thermal characteristics in heat exchange matrices. The heat exchanger geometry evaluated consists of an isotropic open lattice structure containing group-interconnected, millimeter-scale, thermally conductive ligaments. The Reynolds number range of interest is Re = 3-1000. The flow fields investigated in this paper are both laminar and turbulent. The laminar flow fields are solved using direct numerical simulation (DNS), while turbulent flow fields a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Following Gullbrand et al [8], a single unit cell, shown in Fig. 9, was used to perform the numerical simulations.…”
Section: B Computational Domain and Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Gullbrand et al [8], a single unit cell, shown in Fig. 9, was used to perform the numerical simulations.…”
Section: B Computational Domain and Boundary Conditionsmentioning
confidence: 99%
“…They have shown that metal fraction, dimensionless specific surface area and dimensionless effective thermal conductivity can range as: 0≤ 1-ε ≤ 0.94, 0.93 ≤ βD ≤ π and 0 ≤ Ke ≤ π/4. Gullbrand et al [8] considered laminar and turbulent convection in circular cross section filament box lattices. Their work shows that steady laminar flow persists up to at least a Reynolds number of 100, with transition to unsteady flow at a Reynolds number of 300.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The friction factor value increases with increasing level of turbulent kinetic energy. KWM predicts the smallest value of turbulent kinetic energy in the domain and seems to behave more similar to an unsteady flow than to a turbulent flow [4]. The Pearson Product Moment correlation is calculated for the relation between friction factor and volume-averaged turbulent kinetic energy.…”
Section: Friction Factormentioning
confidence: 99%
“…Gullbrand and coworkers [4] have recently reported on single-phase convection in mm-scale box lattices. They found that steady laminar flow persists up to a Reynolds number of 100, with transition to an unsteady flow at a Reynolds number of 300.…”
Section: Introductionmentioning
confidence: 99%